Precambrian evolution and cratonization of the Tarim Block, NW China: Petrology, geochemistry, Nd-isotopes and U–Pb zircon geochronology from Archaean gabbro-TTG–potassic granite suite and Paleoproterozoicmetamorphic belt - Zhang, C.; Li, H.; Santosh, M.; Li, Zheng-Xiang; Zou, H.; Wang, H.; Ye, H. (Pergamon-Elsevier Science Ltd, 2012)
We report field characteristics, petrography, geochemistry and isotopic ages of the Neoarchaean intrusive complex and the Paleoproterozoic metamorphic belt around Quruqtagh in the northern margin of the Tarim Block, NW China in an attempt to evaluate the evolution of the Precambrian basement of the Tarim Block. Zircon U–Pb ages indicate that the tonalite–trondhjemite complex with gabbroic enclaves and the slightly younger potassic granites crystallized at ca. 2.60 Ga and ca. 2.53 Ga respectively, and were metamorphosed at ca.1.85–1.80 Ga. Zircon U–Pb ages indicate that the amphibolite to granulite facies assemblages in the strongly deformed Paleoproterozoic gneiss-schist belt were generated during a major thermal event at 1.85–1.80 Ga, and were again overprinted by late Mesoproterozoic to early Neoproterozoic metamorphism (1.1–0.95 Ga). Geochemically, the gabbros occurring within the tonalite–trondhjemite suite exhibit arc tholeiite signature and their chemical and Nd isotopic compositions suggest that they were derived from partial melting of a metasomatised and depleted mantle.The tonalites and trondhjemites have varied geochemical compositions but both preserve distinct Archaean TTG (tonalite–trondhjemite–granodiorite) signatures. However, the ca. 2.53 Ga potassic granites have very different geochemical compositions as compared to the tonalite–trondjemite suite and show extreme enrichment of LREE and LILE, as well as a marked depletion of HREE and HFSE. Based on the geochemical and geochronological data presented in this contribution, we suggest that: (1) the gabbro–tonalite–trondhjemite suite and the late potassic granites represent an evolution from an arc system through the final collision and late or post-orogenic extension when the potassic granite was emplaced, thus building the cratonic architecture of the proto-crust of the Tarim Block; (2) the ca.1.9–1.8 Ga metamorphism marks an important orogenic event in the crystalline basement of the Tarim Block which was stabilized during the early Precambrian; (3) the 1.9–1.8 Ga and 1.1–0.9 Ga metamorphic ages form part of the global-scale orogeny identified to be related to the Paleoproterozoic Columbia and Neoproterozoic Rodinia supercontinent assemblies.